2017
DOI: 10.3390/s17030449
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis for Biomedical Sciences Applications: A Review

Abstract: Dielectrophoresis (DEP) is a label-free, accurate, fast, low-cost diagnostic technique that uses the principles of polarization and the motion of bioparticles in applied electric fields. This technique has been proven to be beneficial in various fields, including environmental research, polymer research, biosensors, microfluidics, medicine and diagnostics. Biomedical science research is one of the major research areas that could potentially benefit from DEP technology for diverse applications. Nevertheless, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
168
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 203 publications
(220 reference statements)
1
168
0
3
Order By: Relevance
“…Moreover, in a previous study, we demonstrated that the method that we proposed based on negative DEP has high sensitivity that enables detection of as little as 80 molecules, which corresponds to 13 attomolars, per PM combined with the high specificity of an immunoassay with monoclonal antibodies [15,16]. DEP is a force produced by an electric field gradient in dielectric particles [17][18][19][20][21]. Negative DEP is a force produced by an electric field gradient to dielectric particles that is opposite to the direction of the electric field gradient.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, in a previous study, we demonstrated that the method that we proposed based on negative DEP has high sensitivity that enables detection of as little as 80 molecules, which corresponds to 13 attomolars, per PM combined with the high specificity of an immunoassay with monoclonal antibodies [15,16]. DEP is a force produced by an electric field gradient in dielectric particles [17][18][19][20][21]. Negative DEP is a force produced by an electric field gradient to dielectric particles that is opposite to the direction of the electric field gradient.…”
Section: Introductionmentioning
confidence: 98%
“…DEP was first studied and named by Pohl in the 1950s and the capability for biological cell separation was demonstrated in the following decade . From then on, there was an explosive growth on the investigation of DEP‐based cell viability analysis which has wide applications in the fields of medical diagnose , bioscience , environmental biology , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Lee et al surveyed the development of DEP techniques for stem cell sorting and anticipated that DEP will accelerate optimization of protocols for stem-cell usage in regenerative medicine [32]. The relevance of the DEP separation methods is underlined in a significant number of excellent reviews published over the past decade [33][34][35][36][37][38][39]. DEP, as with other marker-free methods used in CTCs enrichment, can control cellular damage or toxicity when an optimized protocol is in place [32].…”
Section: Introductionmentioning
confidence: 99%